Self-Determination to Fight Oppressions as Seen in the Main Character of The Color Purple by Alice Walker - Levita Setya Budi; Dewi Widyastuti (Journal of Language and Literature, 2017)
In several cultures in the world, women usually receive inequality and experience oppression. These experiences are reflected in a literary work by Alice Walker entitled The Color Purple. This novel tells about a woman, named Celie, who is oppressed. However, she fights the oppression by having her self-determination. This study tries to identify how the characteristics of Celie are described, to find out how the oppressions that she experiences are described, and to examine how her self-determination to fight the oppressions are described.The Color Purple proves that self-determination helps women to fight oppression whatever characteristic that they have. Celie is described as an uneducated, submissive, and unattractive woman in the story. She experiences sexual oppressions and non-sexual oppression. She proves that her sexual self-determination, by having a lesbian relationship with Shug, and non-sexual self-determination, leaving her husband to Memphis and running her own business, helps her to fight oppressions that she experiences, and she could live her life without any oppression. Feminist approach and radical feminism theory were used in this study to analyze self-determination to fight oppression of the main character of The Color Purple.Key words: self-determination, oppression, women